2014
DOI: 10.1016/j.febslet.2014.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Gpn1 and Gpn3 associate tightly and their protein levels are mutually dependent in mammalian cells

Abstract: Edited by Ivan SadowskiKeywords: Gpn1 Gpn3 Gpn1-Gpn3 interaction Gpn1-Gpn3 nucleocytoplasmic shuttling Interdependent protein levels shRNA a b s t r a c t Gpn1 and Gpn3 are GTPases individually required for nuclear targeting of RNA polymerase II. Here we show that whereas Gpn3-EYFP distributed between the cytoplasm and cell nucleus, it was mainly cytoplasmic when coexpressed with Gpn1-Flag. Gpn3-Flag retained Gpn1-EYFP in the cytoplasm. However, Gpn3-EYFP/Gpn1-Flag nucleocytoplasmic shuttling was revealed afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 21 publications
(41 reference statements)
6
29
0
Order By: Relevance
“…Gpn3 was reported ubiquitinated on lysine 216, a finding confirmed in a second global study by Mertins et al [10]. Finally, we demonstrated that polyubiquitination of Gpn3 occurred in the cell nucleus and that it was prominent when expressing Gpn3 alone, but that this process was inhibited in a dose-dependent manner by co-transfecting Gpn1, a critical Gpn3 partner in human cells [7]. However, it is necessary to first confirm these results for individual proteins and then determine if this ubiquitination corresponds to mono, multi or polyubiquitination, as well as physiological relevance and regulation.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Gpn3 was reported ubiquitinated on lysine 216, a finding confirmed in a second global study by Mertins et al [10]. Finally, we demonstrated that polyubiquitination of Gpn3 occurred in the cell nucleus and that it was prominent when expressing Gpn3 alone, but that this process was inhibited in a dose-dependent manner by co-transfecting Gpn1, a critical Gpn3 partner in human cells [7]. However, it is necessary to first confirm these results for individual proteins and then determine if this ubiquitination corresponds to mono, multi or polyubiquitination, as well as physiological relevance and regulation.…”
Section: Discussionsupporting
confidence: 87%
“…These results indicate that polyubiquitination on lysine 216 is a regulatory process for proteasomal degradation of Gpn3 that is not in a complex with Gpn1, a critical partner of Gpn3 in mammalian cells [7]. We showed that Gpn3 is polyubiquitinated in the presence of MG132.…”
mentioning
confidence: 82%
See 3 more Smart Citations